Pengaturan Kecepatan Motor Tiga Fasa Dengan Arah Putar Reverse Menggunakan Variabel Speed Drive (VSD): Three-Phase Motor Speed Regulation with Reverse Rotation Using Variable Speed Drive (VSD) - Luthfi, Muhammad Arief (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2022)
Induction motors are the most widely used driving motors in industry. The use of three-phase induction motors is widely found in industry because of their low price, easy maintenance and reliable design, so they are preferred for large-scale engine propulsion. This 3-phase motor uses a Delta/Triangle circuit. Setting the speed of a 3-phase reverse induction motor by setting the frequency value from a minimum value of 5 Hz to 50 Hz with an incremental step of 5 Hz using a Variable Speed ??Drive (VSD), to find out the RPM of the motor there are 2 data results, namely by using a tachometer and on the motor there is an infrared sensor to determine the RPM in the motor, then the data generated by the sensor is processed on the Arduino nano microcontroller circuit and will be displayed on the LCD and the resulting data will be sent by the NodeMCU ESP8266 module to be displayed on a smartphone using the blynk application.